The brain correlates of the effects of monetary and verbal rewards on intrinsic motivation - Albrecht, Konstanze; Abeler, Johannes; Weber, Bernd; Falk, Armin (Frontiers in Neuroscience, 2014)
Apart from everyday duties, such as doing the laundry or cleaning the house, there are tasks we do for pleasure and enjoyment. We do such tasks, like solving crossword puzzles or reading novels, without any external pressure or force; instead, we are intrinsically motivated: We do the tasks because we enjoy doing them. Previous studies suggest that external rewards, i.e., rewards from the outside, affect the intrinsic motivation to engage in a task: While performance-based monetary rewards are perceived as controlling and induce a business-contract framing, verbal rewards praising one’s competence can enhance the perceived self-determination. Accordingly, the former have been shown to decrease intrinsic motivation, whereas the latter have been shown to increase intrinsic motivation. The present study investigated the neural processes underlying the effects of monetary and verbal rewards on intrinsic motivation in a group of 64 subjects applying functional magnetic resonance imaging (fMRI). We found that, when participants received positive performance feedback, activation in the anterior striatum and midbrain was affected by the nature of the reward; compared to a non-rewarded control group, activation was higher while monetary rewards were administered. However, we did not find a decrease in activation after reward withdrawal. In contrast, we found an increase in activation for verbal rewards: After verbal rewards had been withdrawn, participants showed a higher activation in the aforementioned brain areas when they received success compared to failure feedback. We further found that, while participants worked on the task, activation in the lateral prefrontal cortex was enhanced after the verbal rewards were administered and withdrawn.